PENGGUNAAN MEDIA SOSIAL DALAM BELAJAR MANDIRI SISWA KELAS IV MADRASAH IBTIDAIYAH PERSATUAN UMAT ISLAM HAURKOLOT - Samrodin, Samrodin; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
In this era, information is easily accessible and can easily spread throughout the world. One of the products of technological development is the birth of social media (social media). The existence of social media has brought various impacts on the condition of the Indonesian people, especially among students, both in the form of positive and negative impacts. The aims of this study were: 1) to find out the use of social media in independent learning for fourth grade students of Madrasah Ibtidaiyah, Haurkolot Islamic Community Association. 2) To find out the supporting and inhibiting factors for the use of social media in independent learning for fourth grade students of Madrasah Ibtidaiyah, the Haurkolot Islamic Community. This research is a qualitative research. Sources of research data used are primary data sources in the form of information from the field through direct observation by means of interviews, observations and documentation. The results of the study are that: 1) With the existence of social media a) Teachers are helped so that learning efficiency can be achieved. b) Teachers can make schools more qualified so that educational goals can be achieved. c) Students in learning are more independent. d) Students can learn to develop technical and social skills which are much needed in this digital age. e) Increase students' insight about current world news. f) As a medium of da'wah and discussion. g) Students can learn to exchange ideas with friends, and learn from people's words so that they are more responsive and communicative to their surroundings. h) Can be used as a learning medium. 2) And found 5 supporting factors, namely: facilities and infrastructure, finance, assignment, extracurricular activities, and motivation of teachers and students as well as 3 inhibiting factors, namely: time, environment, and the number and nature of students.